Altered activation and functional connectivity in individuals with social anhedonia when envisioning positive future episodes. Issue 16 (29th December 2022) - Yang, Zhuo-ya; Zhang, Rui-ting; Wang, Yong-ming; Huang, Jia; Zhou, Han-yu; Cheung, Eric F. C.; Chan, Raymond C. K.
Abstract: Background: Anticipatory pleasure deficits are closely correlated with negative symptoms in schizophrenia, and may be found in both clinical and subclinical populations along the psychosis continuum. Prospection, which is an important component of anticipatory pleasure, is impaired in individuals with social anhedonia (SocAnh). In this study, we examined the neural correlates of envisioning positive future events in individuals with SocAnh. Methods: Forty-nine individuals with SocAnh and 33 matched controls were recruited to undergo functional MRI scanning, during which they were instructed to simulate positive or neutral future episodes according to cue words. Two stages of prospection were distinguished: construction and elaboration. Results: Reduced activation at the caudate and the precuneus when prospecting positive ( v . neutral) future events was observed in individuals with SocAnh. Furthermore, compared with controls, increased functional connectivity between the caudate and the inferior occipital gyrus during positive ( v . neutral) prospection was found in individuals with SocAnh. Both groups exhibited a similar pattern of brain activation for the construction v . elaboration contrast, regardless of the emotional context. Conclusions: Our results provide further evidence on the neural mechanism of anticipatory pleasure deficits in subclinical individuals with SocAnh and suggest that altered cortico-striatal circuit may play a role in anticipatory pleasure deficits in these individuals.